Theories of International Relations. - Burchill, Scott; Linklater, Andrew; Devetak, Richard (Basingstoke : Palgrave Macmillan, 2013)
The fully updated and revised fifth edition of this widely-used text provides a comprehensive survey of leading perspectives in the field. Updated throughout to take account of major events and developments, such as the Arab Spring, it also includes new material on neo-realism and neo-liberalism, postcolonialism and cosmopolitanism.
Introduction / Scott Burchill and Andrew Linklater -- Realism / Jack Donnelly -- Liberalism / Scott Burchill -- The English school / Andrew Linklater -- Marx and Marxism / Andrew Linklater -- Historical sociology / Andrew Linklater -- Critical theory / Richard Devetak -- Post-structuralism / Richard Devetak -- Constructivism / Christian Reus-Smit -- Feminism / Jacqui True -- Green politics / Matthew Paterson -- International political theory / Terry Nardin.
Includes bibliographical references and index.
Print version record.
Keywords: International relations -- Philosophy; Political science & theory; Society & social sciences; POLITICAL SCIENCE -- Government -- International